Molecular construction of NADH-cytochrome b5 reductase inhibition by flavonoids and chemical basis of difference in inhibition potential: Molecular dynamics simulation study - Verma S.; Singh A.; Mishra A. (My University, 2025)
NADH-cytochrome b5 reductase, a flavoprotein, plays a central role in many diverse metabolic reactions. NADH-cytochrome b5 reductase has been shown to be responsible for the generation of free radicals from heterocyclic amines. Flavonoids compounds share remarkable similarity in structure but showed differences in their cytochrome b5 reductase inhibition pattern. Our molecular dynamics simulation studies revealed that the difference in substitution at C3 position of ring C may lead to difference in interaction with enzyme. Absence of hydroxyl group substitution at C3 in luteolin facilitates the strong cation-p interaction between Lys185 and ring A, and C and p-p between Phe92 and ring A, and C along with h-bonding between Lys185 and oxo group. Ring B of luteolin showed strong π-π interaction with FAD. These interactions were found absent in quercetin and taxifolin. These results suggest that absence of hydroxyl group substitution at C3 increases the potency of flavonoid inhibitors for cytochrome b5 reductase.